OVERCOMING CHALLENGES IN SAFETY MANAGEMENT SYSTEMS TO ENHANCE OPERATIONAL EFFICIENCY IN FUEL STATION OPERATIONS - MOHD SHUKRI, ABDUL WAHAB; Syed Tarmizi, Syed Shazali; Noor Hisyam, Noor Mohamed; Abdul Rani, Achmed Abdullah (School of Engineering. Taylor’s University, 2026)
Effective implementation of Safety Management Systems (SMS) is essential for improving operational efficiency (OE) and reducing risks across modern industries. In particular, the fuel station industry faces heightened safety concerns due to flammable materials, high human traffic, and complex regulatory requirements. Although SMS can decrease faults by 10% to 50% and enhance safety performance, organisations often encounter significant obstacles. These include insufficient leadership commitment, training deficiencies, and cultural barriers that hinder effective SMS deployment. The main problem this study addresses is the persistent gap between SMS design and its actual execution at operational levels within fuel stations. Therefore, the aim of this research is to identify critical implementation challenges in SMS and evaluate their impact on operational efficiency in fuel station operations. This article explores these challenges and presents practical solutions, such as fostering strong leadership engagement, improving training programmes, and implementing structured planning strategies. A qualitative-based methodology was adapted, a narrative review supported by interviews. Key findings revealed that leadership support, employee safety culture, and clear procedural alignment significantly influence SMS success and operational outcomes. By addressing these critical areas, organisations can overcome existing hurdles and create safer, more efficient operations, ultimately achieving sustainable improvements in safety outcomes and operational performance.